Regulating "illegal work" in China - Mimi Zou (United Nations Research Institute for Social Development (UNRISD), 2016)
The Exit and Entry Administration Law 2013 (EEAL) in China has been widely considered to be a major step forward in developing a more comprehensive legal regulatory regime for dealing with the rising inflow of foreigners to the country in recent decades. Situated in a policy discourse aimed at combating the so-called "three illegalities" (sanfei) of illegal entry, residence, and work, the EEAL introduces a range of restrictions on the admission of foreign migrants, controls over their employment and residence, as well as enforcement mechanisms that involve employers and members of the general public. This paper examines the ways in which China's immigration law regime regulates "illegal work" and thereby constructs precarious statuses that shape migrants' vulnerability to precariousness in their employment relations.
Additional information: Addressing Multiple Forms of Migrant Precarity: Beyond “Management” of Migration to an Integrated Rights-Based Approach
Keywords: 330